Tingkat Smartphone Addiction pada Penduduk di Kota Banda Aceh - Rita Fathya; Kartika Sari; Marty Mawarpury; Afriani Afriani (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2020)
The use of smartphones is a basic necessity at this time, but excessive use can lead a bad impact, one of them is smartphones addiction. Smartphone addiction is a form of attachment to smartphones that allows social problems such as withdrawal and daily disturbance. This study aims to determine the level of smartphone addiction on society in Banda Aceh. Using a quantitative design with a survey method, the respondents of this study were 500 people, with sample collection techniques using unrestricted self-selected surveys. Research data collection was obtained using adaptation the Smartphone Addiction Scale Short Version (SAS-SV) by Kwon, dkk. Based on the results of the study it can be seen that the level of smartphone addiction in the population on Banda Aceh society not much different, there are 51.4% subjects with low smartphone addiction levels and 48.6% subjects with high smartphone addiction levels. Chi Square test results showed that there are several demographic variables that contributed to smartphone addiction level (p<0.05), age, education level, occupation, duration of smartphone use on single day, and frequency of smartphone check on single day.